Interleukin‐1 β‐targeted treatment strategies in inflammatory depression: toward personalized care. (15th October 2016) - Ellul, P.; Boyer, L.; Groc, L.; Leboyer, M.; Fond, G.
Abstract : Objectives: It is unknown whether a cytokine signature may help the identification of subgroup of patient who would respond to personalized treatment. As interleukin‐1 beta (Il‐1β) seems to play a major role in mood disorder, a systematic review and meta‐analysis of its potential role in major depressive disorder (MDD) was carried out. Methods: A systematic search was performed to identify appropriate MDD vs. control studies pertaining to Il‐1β. Methodological quality and possible moderators were also assessed. Results: A total of 1922 studies were identified, and 53 articles were selected. Results showed an association between increased blood IL‐1β and MDD in high‐quality studies only. No association with age was found. No IL‐1β gene‐related polymorphisms has been associated with MDD. No effect of antidepressant on IL‐1β level has been found, although the antidepressants investigated were various. Qualitative analyses indicate that MDD coupled to a history of childhood trauma may be a subgroup for IL‐1β ‐targeted therapies. No difference in studies utilizing a stimulation method has been identified to date. Conclusions: The present work has confirmed IL‐1β as a biological marker of interest for innovative MDD treatments. However, further studies are needed to clarify the patients with MDD who may benefit from these therapies.